EFEKTIFITAS APE “RUMAH EDUKASI” TERHADAP KEMAMPUAN KONSEP DASAR HITUNG DAN MENGENAL WAKTU PADA SISWA TAMAN KANAK-KANAK - Rinanti Resmadewi; Dzulkifli Dzulkifli (Universitas Muhammadiyah Gresik, 2025)
Background: The Education House is a learning media in the form of an Educational Game Tools (EGT) which aims to train children in the ability to think logically, increase creativity, and train children's fine motor skills. This game is divided into three kinds, namely games in counting, guessing pictures, and knowing the time by pointing the clock. Objective: to see whether APE is effective in improving the ability to count and recognize time in Aisyiyah Kindergarten students Method: This study used quantitative methods and the research design used was experimental research (one group pretest-posttest design). The research subjects were students of TK Aisyiyah Bustanul Athfal 58, TK Aisyiyah Bustanul Athfal 6, and TK Aisyiyah Bustanul Athfal 47 Surabaya. The data collection technique used in this study was by giving pre-test and post-test questions. Result: after the researchers gave the treatment twice using the EGT